Neuroblastoma and opsoclonus-myoclonus-ataxia syndrome – clinical and pathological characteristics - Stefanowicz, Joanna; Iżycka-Świeszewska, Ewa; Drożyńska, Elżbieta; Pienczk, Jerzy; Połczyńska, Katarzyna; Czauderna, Piotr; Sierota, Danuta; Bień, Ewa; Stachowicz-Stencel, Teresa; Kosiak, Wojciech; Balcerska, Anna (Folia Neuropathologica, 2008)
Introduction: Opsoclonus-myoclonus-ataxia (OMA) syndrome is the most common paraneoplastic neurological syndrome in childhood. Materials and Methods: We reviewed the literature and reported on clinical and pathological characteristics of four children with OMA and peripheral neuroblastic tumours. In two of the children the onset of neurological symptoms was connected with a vaccination and in one with viral infection. The suprarenal gland was the primary localization of the tumour in 3 of the children and in one the tumour was located in the retroperitoneal area. All cases were in stage II or III of the disease, with no metastases or MYCN amplification. The group included two ganglioneuroblastomas, one ganglioneuroma and one differentiating neuroblastoma. The tumours were characterized by the presence of lymphocytic infiltrations with lymphadenoplasia. Immunohistochemical analysis of inflammatory infiltrations revealed mixed type populations of lymphocytes with prevalence of the cytotoxic type (CD8 and CD56-positive cells). The participation of dendritic cells and macrophages was also detected. All patients were treated by surgery alone or with adjuvant chemotherapy with a positive outcome. In 3 cases persistent neurological disorders were observed with exacerbations during infections. Conclusion: In some patients the onset of OMA is related to vaccination or infection. Children with OMA and neuroblastoma despite a good oncological prognosis often present permanent neurological and developmental deficits. The inflammatory infiltrations within the tumours are combined, with predominant participation of cytotoxic cells.